2011
DOI: 10.1210/en.2010-0693
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impacts of Insulin-Like Growth Factor-Binding Protein-3 (IGFBP-3) in Epithelial IGF-Induced Lung Cancer Development

Abstract: The IGF axis has been implicated in the risk of various cancers. We previously reported a potential role of tissue-derived IGF in lung tumor formation and progression. However, the role of IGFbinding protein (IGFBP)-3, a major IGFBP, on the activity of tissue-driven IGF in lung cancer development is largely unknown. Here, we show that IGF-I, but not IGF-II, protein levels in non-small-cell lung cancer (NSCLC) were significantly higher than those in normal and hyperplastic bronchial epithelium. We found that IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Demographic information for those patients was described previously. 16 Formalin-fixed, paraffin-embedded primary NSCLC sections (5 lm thick) were placed in a tissue microarray (TMA). Immunohistochemical (IHC) evaluation of the NSCLC TMA was performed as previously described.…”
Section: Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic information for those patients was described previously. 16 Formalin-fixed, paraffin-embedded primary NSCLC sections (5 lm thick) were placed in a tissue microarray (TMA). Immunohistochemical (IHC) evaluation of the NSCLC TMA was performed as previously described.…”
Section: Protein Analysismentioning
confidence: 99%
“…Immunohistochemical (IHC) evaluation of the NSCLC TMA was performed as previously described. 16 Anti-pIGF-1R (Tyr 1135/1136)/IR (Tyr1162/1163) antibody (Biosource, Camarillo, Calif; diluted 1:200) or anti-pEGFR (Tyr1068) antibody (Zymed Laboratories, San Francisco, Calif; diluted 1:100) was used for staining. Immunostaining for IGF-1R, and pIGF-1R/IR (membrane) was quantified by a lung cancer pathologist who used a 4-value intensity score (0, 1þ, 2þ, and 3þ), and the extent of reactivity was expressed as a percentage.…”
Section: Protein Analysismentioning
confidence: 99%
“…No cases of IGFBP3 gene deletion in humans have been reported, but hypermethylation of the IGFBP3 promoter is involved in loss of IGFBP3 expression in NSCLC, and may be related to the development of acquired treatment resistance (16)(17)(18)(19). Although a prior report has shown that heterozygously deleted Igfbp3 transgenic mice with mutant IGF1 expression have higher lung tumorigenesis, there was no increased tumorigenesis in homozygously deleted Igfbp3 mice compared with wild-type Igfbp3 control, which was unexplained (20). Our previous data from lung cancer cell lines suggested that lung cancer cells express significantly lower levels of IGFBP3 when they develop resistance to cisplatin and radiation (21).…”
Section: Introductionmentioning
confidence: 99%
“…These markers have been investigated using in vitro and in vivo early carcinogenesis models, and were found to be key to the pathogenesis of NSCLC, both adenocarcinoma and squamous cell carcinoma. The markers chosen relate to cell adhesion and extracellular matrix interactions (CASK, CD51 (8), EpCAM (9), SPP1 (10)), inflammation (CXCR2 (11)), growth factors and effector pathways (IGF-1R(12), IGFBP3 (13), insulin receptor (14), pIGF-1R, pEGFR (15, 16)), growth and metabolism (pAkt (17, 18), pSrc (19), pmTor (18), pAMPK (20), pS6 (17), SFN (21), UBE2C), and DNA replication and repair (FEN1, MCM2, MCM6, TPX2 (21, 22)). We then aimed to investigate these biomarkers in early stage lung cancer and to gain a better understanding of the cellular and molecular processes that drive lung carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%